Formation of a Displaced Plasma Wake at Neptune's Moon Triton. Issue 1 (4th January 2022) - Simon, Sven; Addison, Peter; Liuzzo, Lucas
Abstract: A prominent feature of the interaction between a planetary moon and its magnetospheric environment is the formation of a wake cavity in the downstream hemisphere, characterized by a significant decrease of the incident plasma density. Using an analytical model of Triton's sub‐Alfvénic interaction with Neptune's magnetosphere, we demonstrate that this moon's wake may be rotated away from its downstream hemisphere into a region that would be accessible to the undisturbed upstream flow. Due to the strong tilt of Neptune's magnetospheric field and the low Alfvénic Mach number of the plasma, one of Triton's Alfvén wings can penetrate into the upstream region and intercept the impinging plasma long before it reaches the moon. The interaction with this upstream wing causes the flow to be deflected toward Triton at a steep angle before being absorbed, thereby generating a wake cavity that is significantly displaced with respect to the moon's geometric plasma shadow. Along the downstream‐facing wing, the flow is deflected away from Triton and therefore unable to refill the displaced wake. Since the ionospheric Pedersen conductance greatly exceeds the Alfvén conductance, this asymmetric flow deflection is particularly intense at Triton: when the plasma encounters the wings, it is channeled toward or away from the moon along the axes of the wing tubes. The deflection of the streamlines away from their upstream direction peaks in the range of plasma parameters found along Triton's orbit. Therefore, the displaced wake may be a persistent feature of this moon's plasma interaction and observable during future flybys. Plain Language Summary: Many moons in the outer solar system are embedded in their parent planet's magnetospheres where they are continuously exposed to a flow of magnetized plasma. In general, the partial blockage of this flow by a moon's solid body and ionosphere generates a depletion region at the downstream side where the plasma density is significantly reduced. In addition, the interaction between a moon and its plasma environment triggers non‐linear (Alfvén) waves that mainly propagate along the magnetospheric magnetic field. At many large moons of Jupiter and Saturn, the magnetospheric field is nearly perpendicular to the incident flow direction, that is, these waves cannot reach the upstream region. However, Neptune's magnetic field near Triton possesses a strong component along the plasma flow. Therefore, the waves may travel toward upstream and commence deflecting the incident flow before it even comes close to the moon. Since this deflection forces the plasma particles onto highly inclined trajectories toward Triton, their subsequent absorption generates a wake cavity that is no longer located "behind" the moon. Such a displaced wake may be observable during future missions to the Neptune‐Triton system and may represent a unique feature in the diverse "zoo" of moon‐magnetosphere interaction scenarios at the outer planets. Key Points: Based on an analytical model, we study the plasma flow deflection caused by Triton's sub‐Alfvenic interaction with Neptune's magnetosphere One of Triton's Alfven wings may be oriented toward upstream, initiating the deflection of the incident flow long before it reaches the moon Absorption of the deflected upstream plasma at Triton generates a wake cavity that is displaced away from the moon's geometric plasma shadow